2014
DOI: 10.1007/s10928-014-9358-0
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients

Abstract: Intravenous acetaminophen is a commonly used analgesic following surgery. The aims of this study were to determine the population pharmacokinetic profile of intravenous acetaminophen and its metabolites in adult surgical patients and to identify patient characteristics associated with acetaminophen metabolism in the postoperative period. 53 patients were included in the dataset; 28 were men, median age (range) 60 years (33-87), median weight (range) 74 kg (54-129). Patients received 1, 1.5 or 2 g of intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…acetaminophen have been reported in different study settings. In studies of perioperative patients, age and sex [13], and age and creatinine clearance [3] were found to affect PK parameters. In a PK analysis using a pooled historical dataset from past PK studies, including not only perioperative patients but also healthy volunteers, intensive care unit patients, and perinatal women, Allegart et al [4] concluded that size, including an allometrically scaled body weight and normal fat mass (extension of the concept of predicted normal weight), and age were important covariates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…acetaminophen have been reported in different study settings. In studies of perioperative patients, age and sex [13], and age and creatinine clearance [3] were found to affect PK parameters. In a PK analysis using a pooled historical dataset from past PK studies, including not only perioperative patients but also healthy volunteers, intensive care unit patients, and perinatal women, Allegart et al [4] concluded that size, including an allometrically scaled body weight and normal fat mass (extension of the concept of predicted normal weight), and age were important covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Simulations of 1 g of intravenous acetaminophen administered to patients with different body weights using the current model (a) and previous models reported by Würthwein et al[2] (b), Wang et al[6] (c), and Owens et al[3] (d). Horizontal dot lines are assumed to be the lower limit of the therapeutic range (10 μg/mL[10]) Simulations of 1 g of intravenous acetaminophen (ACET) administered to patients (weight 67 kg) over different durations using the current model.…”
mentioning
confidence: 89%
See 3 more Smart Citations